The Law Enforcement Policy On Traffic Accident By Police - Cahyo Dwi Prakosa; Umar Ma'ruf; Achmad Sulchan (Law Development Journal, 2022)
The purpose of this research is to find out and analyze the law enforcement against traffic accidents by the police in the jurisdiction of the Batang Resort Police. To know and analyze the factors that hinder the settlement of traffic accident casesin the jurisdiction of the Batang Resort Police. To know and analyze the law enforcement policies by the police to handle traffic accidents in the jurisdiction of the Batang Resort Police. This study uses a sociological juridical approach, with a descriptive analytical research specification. The data used in this study are secondary data obtained from literature study. The data were analyzed in a qualitative juridical manner. The results of this study are Law Enforcement Against Traffic Accidents by the Police is law enforcement can be done penal and non-penal. Law enforcement efforts through the penal route focus more on the repressive nature (oppression/eradication/suppression) after the crime has occurred, while the non-penal route focuses more on the preventive nature (enforcement/deterrence/control) before the crime occurs. Basically law enforcement is the implementation of criminal policy (criminal policy) by using criminal policies carried out through the mechanism of the criminal justice system (criminal justice system).The factors that hinder the settlement of traffic accident cases are: Summoning or Presenting a Witness and Factors Lack of Legal Knowledge. Policies for Law Enforcement by the Police for Handling Traffic Accidents are by conducting blue patrols at violator-prone hours on the road, conducting cross patrols, socialization (security, safety, traffic order to road users), and installing banners at traffic accident-prone points.